Redefinition of Masculinity based on the Aims of Education - Shi, Ruijia (Transactions on Social Science, Education and Humanities Research, 2023)
The recent phenomenon of feminization in Chinese adolescent boys, characterized by concerns related to qualities like inferiority, cowardice, and weakness, has gained widespread attention. In response, there have been proposals to bolster the masculinity of young males, chiefly through strategies such as increasing the presence of male educators and emphasizing physical education. This paper engages with the intricate landscape of this issue by investigating the evolving concept of masculinity in contemporary society and the burgeoning acceptance of gender diversity. Furthermore, it conducts a critical examination of the stigmatization of femininity and the contentious use of physical education as a determinant of masculinity. Rooted in the educational aims theory of Michael Reiss and John White, this study analyzes the educational objectives associated with nurturing masculinity among adolescent males. Ultimately, it contends that reducing masculinity to mere physical strength is overly simplistic and advocates for a more nuanced and inclusive approach to promote masculinity among Chinese boys. The study underscores the need for comprehensive deliberation and dialogue among government authorities and educators regarding the delineation and enhancement of masculinity in the context of modern Chinese society.